2012
DOI: 10.1890/11-0426.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity promotes ecosystem stability

Abstract: Abstract. Ecosystem stability in variable environments depends on the diversity of form and function of the constituent species. Species phenotypes and ecologies are the product of evolution, and the evolutionary history represented by co-occurring species has been shown to be an important predictor of ecosystem function. If phylogenetic distance is a surrogate for ecological differences, then greater evolutionary diversity should buffer ecosystems against environmental variation and result in greater ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
350
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(372 citation statements)
references
References 61 publications
15
350
0
7
Order By: Relevance
“…This indicates independent statistical effects of species richness and phylogeny, and that the diversity of evolutionary lineages is more important than species richness alone, despite the weakly positive relationship between both measures of diversity. Our results support the accumulating evidence that a plant community's PD is a strong predictor for the strength of ecosystem processes in that community [20,49]. For example, Parker et al [50] demonstrated that the susceptibility of a plant species to diseases and invasion potential (via escape from diseases) is predicted well by the PD of the surrounding plant community.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates independent statistical effects of species richness and phylogeny, and that the diversity of evolutionary lineages is more important than species richness alone, despite the weakly positive relationship between both measures of diversity. Our results support the accumulating evidence that a plant community's PD is a strong predictor for the strength of ecosystem processes in that community [20,49]. For example, Parker et al [50] demonstrated that the susceptibility of a plant species to diseases and invasion potential (via escape from diseases) is predicted well by the PD of the surrounding plant community.…”
Section: Discussionsupporting
confidence: 88%
“…Phylogenetic measures of biodiversity were pioneered by Faith 11 , who developed the concept of phylogenetic diversity (PD), which has been increasingly explored in recent years [12][13][14][15] . Faith et al 12 and Rosauer et al 16 then established phylogenetic concepts of endemism.…”
mentioning
confidence: 99%
“…In this study, we showed that while PDss is strongly correlated with SR (see also Forest et al, 2007;Cadotte et al, 2012), communities can vary greatly in their deviation from expected PD given SR, as measured by ses.PDss. While communities in the central and western Amazon have the greatest tree species richness in the basin (ter Steege et al, 2003), the central Amazon shows much lower phylogenetic diversity than expected given its species richness (ses.PDss) compared to the western Amazon (Fig.…”
Section: Conservation Prioritiesmentioning
confidence: 54%